Pengaruh Ivabradin terhadap Variabilitas Detak Jantung pada Gagal Jantung dengan Fraksi Ejeksi Rendah Akibat Penyakit Jantung Koroner - Kurnia, Handy; Limantoro, Charles; Silitonga, Friska Anggraini Helena; Setiawan, Andreas Arie (UI Scholars Hub, 2025)
Introduction. Heart failure is one of the major challenges in global health due to its significant contribution to morbidity and mortality. One of the pathophysiological aspects is autonomic nervous system dysfunction which can be monitored through heart rate variability (HRV) parameters. Ivabradine is a pharmacological agent that potentially improves the balance of sympathetic and parasympathetic tone. This study was designed to evaluate the impact of ivabradine administration on HRV parameters in heart failure with reduced ejection fraction (≤40%) due to coronary heart disease in Indonesian population. Methods. This study used a quasi-experimental research type with a pretest and posttest method without control which was conducted at Dr. Kariadi Hospital from October 2024 to February 2025. Sixteen patients diagnosed with heart failure with reduced ejection fraction due to coronary heart disease underwent intervention in the form of ivabradine administration at a fixed dose of 5 mg twice a day for 30 days. Evaluation of HRV was carried out through 24 hours holter recording before and after therapy. The HRV parameters analyzed included SDNN, SDANN, RMSSD, pNN50, and LF/HF ratio. Data processing was carried out using a paired t-test for normal distribution and the Wilcoxon Signed-Rank test for non-normal data. P value <0.05 was considered statistically significant. Results. A total of 16 subjects participated in this study, consisting of 14 men (87.5%) and 2 women (12.5%), with a mean age of 57 years. There was a significant increase in SDNN of 14.71 (SD 24.15) milliseconds (p = 0.028), SDANN of 56.99 (SD 26.94) milliseconds (p < 0.001), RMSSD of 18.39 (SD 27.05) milliseconds (p = 0.007), and pNN50 of 6.96% (SD 7.87) (p < 0.001), as well as a decrease in the LF/HF ratio of 1.42 (SD 0.85) (p < 0.001) after 30 days of ivabradine therapy. Conclusions. The administration of ivabradine had a significant effect on improving heart rate variability parameters in both the time and frequency domains in patients with heart failure with reduced ejection fraction due to coronary heart disease. These findings indicate enhanced parasympathetic dominance and reduced sympathetic nervous system activity.